The Effect Of Health Education With Pocketbooks And First Aid Simulation Regarding Ankle Sprain Injurieson The Knowledge And Skills Of Badminton Group Members In Windujaya Village - Nazilatul Munawaroh; Nurul Fatwati Fitriana (Universitas Negeri Gorontalo, 2023)
Background: Sports injuries are caused by physical stress, technical errors, collisions, or physical activities that exceed the training load. Preventive actions are required to minimize the occurrence of ankle injuries. Knowledge of injuries in sports is necessary for athletes and those who carry out sports activities, thus they can perform or provide first aid appropriately and quickly. Besides, they can prevent the occurrence of injuries towards themselves and others. Objective: This research aims to determine the effect of health education with first aid pocket book regarding ankle sprain injuries on the knowledge and skills of badminton group members in Windujaya Village. Methods: This was quantitative researchwith a pre-experimental design and a one-group pre-test-post-test approach. A total of 34 badminton players in windujaya village were selected as the research samples using purposive sampling technique. Results: The average scores of knowledge of badminton group members before and after being given health education were 9.53 + 1.482 and 12.00 + 2.387, respectively. While the average scores of skills before dan after being given health education were 4.71 + 0.928 and 5.91 + 1.357, respectively. The results of the t-test on the level of knowledge and skills showed that the p value was 0.001. Conclusion: There is an effect of health education with first aid pocketbooks and simulation on ankle sprain injuries on the level of knowledge and skills of badminton group members in windujaya village.